Agronomic Challenges and Opportunities for Smallholder Terrace Agriculture in Developing Countries - Chapagain, Tejendra; Raizada, Manish N. (Frontiers in Plant Science, 2017)
Improving land productivity is essential to meet increasing food and forage demands in hillside and mountain communities. Tens of millions of smallholder terrace farmers in Asia, Africa, and Latin America who earn $1-$2 per day do not have access to peer-reviewed knowledge of best agronomic practices, though they have considerable traditional ecological knowledge. Terrace farmers also lack access to affordable farm tools and inputs required to increase crop yields. The objectives of this review are to highlight the agronomic challenges of terrace farming, and offer innovative, low-cost solutions to intensify terrace agriculture while improving local livelihoods. The article focuses on smallholder farmers in developing nations, with particular reference to Nepal. The challenges of terrace agriculture in these regions include lack of quality land area for intensive agriculture, erosion and loss of soil fertility, low yield, poor access to agricultural inputs and services, lack of mechanization, labour shortages, poverty, and illiteracy. Agronomic strategies that could help address these concerns include intensification of terraces using agro-ecological approaches along with introduction of light-weight, low-cost, and purchasable tools and affordable inputs that enhance productivity and reduce female drudgery. To package, deliver, and share these technologies with remote hillside communities, effective scaling up models are required. One opportunity to enable distribution of these products could be to ‘piggy-back’ onto pre-existing snackfood/cigarette/alcohol distribution networks that are prevalent even in the most remote mountainous regions of the world. Such policies, practices, and tools could be supported by formalized government policies dedicated to the well-being of terrace farmers and ecosystems, to maintain resiliency at a time of alarming climate change. We hope this review will inform governments, non-governmental organizations, and the private sector to draw attention to this neglected and vulnerable agro-ecosystem in developing countries.